It starts from home? Explaining environmentally responsible resource and waste management - Brož, David; Čábelková, Inna; Hlaváček, Martin; Smutka, Luboš; Procházka, Petr (Frontiers in Environmental Science, 2023)
Resource and waste management are indispensable to environmentally conscious action and a large part of EU Green politics. Little is known about factors affecting individual propensity for resource and waste management. The article examines the effects of environmental concerns, perceptions of climate change, preferences for EU integration, and media exposure (traditional and new) on the propensity to save resources and waste management employing a representative sample of 904 respondents in the Czech Republic. Methodologically we rely on principal component analysis, correlations, and a set of ordinal regression analyses. The results suggest that environmental and climate concerns increase the propensity to save resources and separate waste. The preferences for EU integration and media exposure were unrelated to saving resources and waste management, except exposure to online news, which negatively affected the environmentally motivated reduction of unnecessary car trips. The results imply immense consequences on the conceptual and policymaking levels. On the conceptual level the results suggest, that the mass media stopped to fulfill its developmental and persuasive functions, as generally people do not relate their pro-environmental behavior to the mass media exposure. From the policy-making perspective the mass media proves to be a poor resource for the pro-environmental actions as in case of social networks the role of mass media on waste management proved negative. We also suggest that saving resources and waste management stopped to be a topic of political and media influence but transferred to the domain of personal values and economic decisions.